2000
DOI: 10.1074/jbc.275.21.15992
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Exonic Regulatory Elements for Muscle-specific Alternative Splicing during Myogenesis and Cardiogenesis

Abstract: Muscle-specific isoform of the mitochondrial ATP synthase ␥ subunit (F 1 ␥) was generated by alternative splicing, and exon 9 of the gene was found to be lacking particularly in skeletal muscle and heart tissue. Recently, we reported that alternative splicing of exon 9 was induced by low serum or acidic media in mouse myoblasts, and that this splicing required de novo protein synthesis of a negative regulatory factor (Ichida, M., Endo, H., Ikeda, U., Matsuda, C., Ueno, E., Shimada, K., and Kagawa, Y. (1998) J.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…Several studies have also indicated that cis-acting elements within exons can function as splicing enhancers and contribute to the accuracy and efficiency of alternative splicing when bound by specific trans-acting factors (30 -32). Purine-rich splicing enhancer sequences (ESEs) have been identified in exons from a number of different tissue-specific or developmentally regulated precursor mRNA species (33,34). These and other degenerate short RNA sequences, which are recognized by one or more SR proteins, are capable of influencing 5Ј-and 3Ј-splice site selection by affecting the activity of weak splice sites in adjacent introns (32,35,36).…”
mentioning
confidence: 99%
“…Several studies have also indicated that cis-acting elements within exons can function as splicing enhancers and contribute to the accuracy and efficiency of alternative splicing when bound by specific trans-acting factors (30 -32). Purine-rich splicing enhancer sequences (ESEs) have been identified in exons from a number of different tissue-specific or developmentally regulated precursor mRNA species (33,34). These and other degenerate short RNA sequences, which are recognized by one or more SR proteins, are capable of influencing 5Ј-and 3Ј-splice site selection by affecting the activity of weak splice sites in adjacent introns (32,35,36).…”
mentioning
confidence: 99%
“…Moreover, because the transgene was more widely expressed than the Ig gene, it could be seen that neither of the splicing patterns in resting or lipopolysaccharide-stimulated B cells represented a default or regulated state. Analysis of transgene tissue-specific splicing has been carried out for exon 9 of the F1␥ gene (38). However, only two mutant minigenes were tested in transgenic animals so that a direct comparison with a wild type construct could not be made.…”
Section: Figmentioning
confidence: 99%
“…11 These elements become particularly important in the presence of weak splice sites or in alternative splicing. 12,13 Exonic splicing enhancers (ESEs) and exonic splicing silencers (ESSs), which are ubiquitous in both constitutively and alternatively spliced exons, account for some of these signals. 14,15 ESEs act as binding sites for serine/ arginine-rich (SR) proteins, a family of highly conserved and structurally similar splicing factors that act at multiple steps of the pre-mRNA splicing pathway.…”
Section: Introductionmentioning
confidence: 99%